Developing Sustainable Urban Mobility Policy on Car Sharing and Carpooling Initiatives - Kyrgyzstan - United Nations Economic Commission for Europe (United Nations, 2023)
This publication is issued in the framework of a project aiming at strengthening the capacity of Central Asian countries to develop sustainable urban mobility policy on car sharing and carpooling initiatives. It targets policy makers from Kyrgyzstan seeking to set up and regulate such initiatives at the national and local levels. This publication provides information on the economic and legal context related to urban mobility and recommendations on the possible measures that can support the development of car sharing and carpooling activities in Kyrgyzstan.